Progressive Design and Evaluation of Primary School Chinese Homework Based on Core Competencies - Li, Jingjing (Journal of Educational Research and Policies, 2025)
In the context of educational reform oriented towards core competencies, primary school Chinese homework, as a key carrier connecting classroom teaching and after-school practice, needs to break through the limitations of traditional fragmentation and mechanization in its design and evaluation, and move towards a transformation towards progression and competency-based learning. Based on the requirements of core competencies in the “Compulsory Education Chinese Curriculum Standards (2022 Edition)” and combined with the theory of learning progression, this article constructs a three-in-one primary school Chinese homework progression system of “goal - task - evaluation”: in terms of goal positioning, it anchors the four core competencies of cultural confidence, language application, thinking ability, and aesthetic creation, and refines the progression gradient for different learning stages; in task design, it takes “basic consolidation - practical application - migration and innovation” as the logical main line, combines five major areas of literacy, writing, reading, writing exercises, oral communication, and comprehensive learning, and develops a contextualized and structured homework chain; in evaluation implementation, it integrates process evaluation and performance evaluation, adopts evaluation tools with multiple subjects and multi-dimensional indicators, and realizes “promoting learning and teaching through evaluation”. The research aims to provide an operable homework design framework for primary school Chinese teachers and promote the implementation of core competencies in after-school learning.